Early Clinical Outcomes of the Active Seal Technology of the AFX Endovascular Aortic Aneurysm System With the VELA Cuff for Patients With a Conical Proximal Neck. (February 2023) - Fujimura, Naoki; Obara, Hideaki; Nagano, Takaaki; Ogawa, Yukihisa; Kobayashi, Taira; Ohmine, Takahiro; Ozeki, Yasuhiro; Sakaguchi, Shoji; Yamaoka, Terutoshi; Ueda, Hideki; Sumi, Makoto; Taniguchi, Satoshi; et al.
Purpose: To evaluate the efficacy of the Active Seal technology employed in the AFX endovascular aortic aneurysm system (AFX), during endovascular aneurysm repair (EVAR) in patients with abdominal aortic aneurysms (AAAs) having a conical proximal neck. Materials and Methods: A retrospective analysis of the EVAR for AAA with a conical proximal neck using the AFX was performed at 17 Japanese hospitals between January 2016 and August 2020. The conical proximal neck was defined as a cone-shaped proximal neck, with more than 10% diameter increase within a 15 mm length at the proximal landing zone. All anatomical analyses were performed in the core laboratory, and cases with parallel walls within the proximal neck adequate for the landing zone were excluded from the study. Results: This study included 53 patients, but only 39 patients (mean age, 76.6 ± 6.7 years; 87.0% males; mean aneurysm diameter, 52.0 ± 8.0 mm) were analyzed after being characterized as having a pure conical neck by the core laboratory. The mean proximal neck diameters at the lower renal artery and proximal edge of the aneurysm were 20.0 ± 2.9 mm and 27.5 ± 4.9 mm, respectively. The mean proximal neck length was 21.5 ± 6.0 mm. Instructions for use violations other than the conical neck were observed in 15 patients (38.5%). The VELA cuff was used in all cases; however, additional proximal cuff was required in 9 more cases (23.1%). The Active Seal technology was able to significantly extend the proximal sealing zone from 21.5 ± 6.0 to 26.0 ± 12.2 mm ( p = .047). Thirty-six patients completed the 12-month follow-up (one patient was lost to follow-up, and 2 patients died from causes unrelated to the aneurysm), and there were no type-1a and 3 endoleaks with only one reintervention (2.6%) related to type 1b endoleak in the 12-month period. Furthermore, there was no significant enlargement of the proximal neck diameter at 12 months (at 1 month: 20.6 ± 3.4 mm and at 12 months: 21.3 ± 3.8 mm; p = .420). Conclusion: The Active Seal technology of the AFX significantly extended the proximal seal zone and no type-1a endoleak and proximal neck dilation was observed in patients with conical proximal neck at 12 months.